Disparate effects of antibiotic-induced microbiome change and enhanced fitness in Daphnia magna. - Asa Motiei; Björn Brindefalk; Martin Ogonowski; Rehab El-Shehawy; Paulina Pastuszek; Karin Ek; Birgitta Liewenborg; Klas Udekwu; Elena Gorokhova (PLoS ONE)
It is a common view that an organism's microbiota has a profound influence on host fitness; however, supporting evidence is lacking in many organisms. We manipulated the gut microbiome of Daphnia magna by chronic exposure to different concentrations of the antibiotic Ciprofloxacin (0.01-1 mg L-1), and evaluated whether this affected the animals fitness and antioxidant capacity. In line with our expectations, antibiotic exposure altered the microbiome in a concentration-dependent manner. However, contrary to these expectations, the reduced diversity of gut bacteria was not associated with any fitness detriment. Moreover, the growth-related parameters correlated negatively with microbial diversity; and, in the daphnids exposed to the lowest Ciprofloxacin concentrations, the antioxidant capacity, growth, and fecundity were even higher than in control animals. These findings suggest that Ciprofloxacin exerts direct stimulatory effects on growth and reproduction in the host, while microbiome- mediated effects are of lesser importance. Thus, although microbiome profiling of Daphnia may be a sensitive tool to identify early effects of antibiotic exposure, disentangling direct and microbiome-mediated effects on the host fitness is not straightforward.